2010
DOI: 10.1093/annonc/mdp364
|View full text |Cite
|
Sign up to set email alerts
|

Standard treatment of female patients with breast cancer decreases substantially for women aged 70 years and older: a German clinical cohort study

Abstract: Our study confirms that substandard treatment increases considerably with age. Omission of radiotherapy had the greatest impact on OAS and DFS in the elderly population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
78
0
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 24 publications
7
78
0
9
Order By: Relevance
“…Several analyses of the registry data have been published so far [16][17][18][19][20], showing, for example, that recurrence-free survival (RFS) and overall survival (OAS) are significantly impacted by guideline-adherent chemotherapy in intermediate and highrisk patients (according to St. Gallen and Nottingham Prognostic Index) and by endocrine therapy in patients with HR (ER)-positive breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Several analyses of the registry data have been published so far [16][17][18][19][20], showing, for example, that recurrence-free survival (RFS) and overall survival (OAS) are significantly impacted by guideline-adherent chemotherapy in intermediate and highrisk patients (according to St. Gallen and Nottingham Prognostic Index) and by endocrine therapy in patients with HR (ER)-positive breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The preferred therapeutic management of women with breast cancer aged over 65 corresponds to the concepts formulated for younger patients and complies with the concepts outlined in the S3 Guidelines [8] and the therapy recommendations formulated by AGO [9]. However, as was recently reported by Hancke et al, only some of the elderly patients in Germany receive therapy which complies with the guidelines [10]. Another recent study by Sautter-Bihl et al reviewed the literature on "elderly patients and breast cancer" and came to the conclusion that "female patients with a life expectancy of more than 5 years and not very extensive co-morbidities should receive adjuvant chemotherapy, trastuzumab and radiation in accordance with current standards, while frail elderly women should receive reduced or no adjuvant standard therapy" [11].…”
Section: Zusammenfassungmentioning
confidence: 83%
“…Many studies also found that there are associations between age and patient-related, physician related and guideline adherent treatments, that influence survival parameter (30)(31)(32). While consensus recommends the use of breast MRI in high risk patients, for staging evaluation to define extent of cancer and identify synchronous lesions (Grade 2B Recommendation by the NCCN)(33) remains controversial.…”
Section: Discussionmentioning
confidence: 99%